Implementasi Customer Relationship Management (CRM) Pada Praja Vape Store Berbasis Sistem Pelayanan Booking Antrian Service - Gustina, Dian; Ashar, Faza Azani (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Praja Vape Store is an offline shop engaged in selling electric cigarettes or often called vape, beside on that Praja Vape Store also provides service device vape services. At this time the vape service queue at Praja Vape Store still does not use the booking service system so when many visitors come to do the vape service, they have to wait quite a long time. In addition, when the customer’s device has been received by the Praja Vape Store for repair, the customer does not know whether their device has been repaired or not and the customer also does not know what spare parts were replaced during the service. this problem can cause the service provide by the Praja Vape Store to its customers to be not good so customer can feel dissatisfied with the service provide. One of the methods used to overcome problems that occur at Praja Vape Store is to implement customer relationship management (CRM) based on booking queuing service. Based on this description, the authors designed a service queuing booking website, a service queuing booking website designed by the author, the customer can make a reservation first before doing the service so that the customer does not have to wait long when they want to do the service and also the customer can find out the status of their vape device that is being repaired. In addition, the customer can find out what spare parts are used to repair their device.